Sumber manusia dan kelebihan daya saing lokasi industri barangan elektrik dan elektonik: kes Zon Perindustrian Bayan Lepas, Pulau Pinang - Nooriah Yusof,; Katiman Rostam, (Universiti Kebangsaan Malaysia, 2008)
The quality of labour force is a major factor in influencing the competitiveness of individual companies as well as an essential prerequisite for developing industrial clusters. Human resource supply in many developing countries including Malaysia is abundant and relatively cheap. Despite these accomplishments, labour force in developing countries is generally perceived as lacking in technical and soft skills which now become major constraints for these countries in attracting foreign investors. The purpose of this article is to discuss and evaluate to what extent the quality of labour influence the competitiveness of Bayan Lepas lndustrial Zone in Penang, as a preferred location for manufacturing activities especially in electrical and electronic (E & E) sectox Evaluation of quality of labour is based on the firm's perception and the responses ffom industrial workers in the E & E sector ofBayan Lepas, Penang. Using secondary data together with data collected through survey and interview methods on 22 jm and 204 industrial employees, the present study indicates that Bayan Lepas has a pool of relatively skilled and competent workforce. Howevel; their quality is stillat an average level. The unsatisfactory level of labour quality can affect the reputation of local labour market and competiveness of Bayan Lepas as preferred location for manufacturing activities. Majority of the firms cited lack of commitment towards organisation and creativity among workers as major weaknesses in labour quality. The firms' perception is supported by the results of the survey among the majority of industrial workers who admit that they lack those aspects. These weaknesses have to be appropriately addressed by the authorities concerned if Bayan Lepas is to continue to be a competitive location for manufacturing activities especially in E & E sector.